Pengaruh Citra Merek, Desain, dan Fitur Produk terhadap Keputusan Pembelian Handphone Nokia (Studi Kasus pada Mahasiswa Universitas Diponegoro) - Alana, Aditya Yessika; Hidayat, Wahyu; Widodo, Handoyo Djoko (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
The purpose at this research is to determine how much the influence of brand image, product design and features of the product Nokia to the purchasing decisions at Diponegoro Universit students, Semarang. Type of this research is eksplanatory research. A sample of 100 respondent was taken that consumers who use Nokia product and also a student of Diponegoro University, and it was taken by accidental sampling technique. Data analysis techniques using linier regression analysis and SPSS 20 version. The survey results revealed that significantly brand image has a positive effect which means any changes to our brand image will influence the purchasing decisions of Nokia products, this is indicated by the regression coefficient of 0.583. In addition, significantly product design has a positive effect, this is indicated by the regression coefficient of 0.484, and for product features significantly has positive influence on purchase decisions, this is indicated by the regression coefficient of 0,798. While simultaneously, brand image, design and product features has a positive influence on purchase decisions as indicated by the linear regression of brand image at 0.365, 0.108 for the product design and product features at 0.396.